PEMANFAATAN KULIT Musa paradisiaca DAN Musa acuminata SEBAGAI MEDIA PERTUMBUHAN Rhizopus sp. DAN Saccharomyces cerevisiae: UTILIZATION OF Musa paradisiaca AND Musa acuminata SKIN AS A GROWTH MEDIA FOR Rhizopus sp. AND Saccharomyces cerevisiae - Anggi Wahyu Santoso; Evy Ratnasari Ekawati; Setyo Dwi Santoso; Deni Harmoko (Jurnal SainHealth, 2024)
Banana peels contains simple sugars and complex sugars which can be utilized in metabolism of microorganisms. This means that banana peels can be used as an alternative culture medium for microorganisms. Rhizopus sp. and Saccharomyces cerevisiae is a type of microbe that often found in nature, and is one type of microbe that can be used in the food and non-food industries. In general, fungi need nitrogn, carbon, vitamins and growth factors. In this research, two types of fungi were grown on the Musa paradisiaca peels (pisang tanduk) and Musa acuminata peels (pisang kepok), as well as potato dextrose agar as a control medium. Growth was observed 24, 48 and 72 hours after inoculation. The data obtained is a qualitative data and analyzed descriptively. We found that the growth results on alternative medium using M. acuminata were quite good for Rhizopus sp. and S. cerevisiae. Meanwhile, medium using M. paradisiaca more suitable for the growth of Rhizopus sp. Keywords: Musa paradisiaca peels, Musa acuminata peels, Rhizopus sp., Saccharomyces cerivisiae